Polar Amplification Model Intercomparison Project - Main results and lessons learned - Semmler, Tido; Streffing, Jan; Jung, Thomas (Zenodo, 2021)
Presentation at the IUP (Institute for Environmental Physics at University of Bremen) - AWI (Alfred Wegener Institute) block seminar on "Polar Amplification" on 30.09.2020 online. The main result of the coordinated atmosphere-only experiments carried out within the Polar Amplification Model Intercomparison Project (PAMIP) is that regional details of an atmospheric response to declined Arctic sea ice are not robust. Also very high horizontal and vertical resolutions do not change this conclusion. Differences between 100 ensemble member packs within a 300 member ensemble are as large as differences between different resolutions.